1994
DOI: 10.1016/0002-9149(94)90102-3
|View full text |Cite
|
Sign up to set email alerts
|

Placement of electrode catheters into the coronary sinus during electrophysiology procedures using a femoral vein approach

Abstract: TC. Efficacy and safety of quinidine therapy for maintenance of sinus rhythm after cardioversion: a metaanalysis of randomized control trials. Circulafion 1990,82:110~1116. 4. The Stroke Prevention in Atria1 Fibrillation (SPAF) Investigators. Stroke prevention in atria1 fibrillation study: final results. Circulation 1991;84:527-539. 5. Bazett HC. An analysis of the time-relations of the electrocardiogram. Heart 1920;7:353. 6. Lopez AJ, Harold JG, Rosenthal MC, Oseran DS, Schapira JN, Peter T. QT prolongation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In view of the above, peripheral venous access may be considered as an alternative venous access option for CS cannulation. The inferior vena cava approach, through the femoral route, is being used as an alternative to superior vena cava access, in an effort to avoid the complications associated with jugular or subclavian vein puncture and decrease patient discomfort during EP procedures [5,6]. However, everyday practice has shown that, due to anatomic reasons, the transfemoral cannulation of the CS using simple fixed curve electrode catheters is a rather difficult task with uncertain success, although steerable catheters may increase success rates of transfemoral CS catheterization [5,7].…”
Section: Discussionmentioning
confidence: 99%
“…In view of the above, peripheral venous access may be considered as an alternative venous access option for CS cannulation. The inferior vena cava approach, through the femoral route, is being used as an alternative to superior vena cava access, in an effort to avoid the complications associated with jugular or subclavian vein puncture and decrease patient discomfort during EP procedures [5,6]. However, everyday practice has shown that, due to anatomic reasons, the transfemoral cannulation of the CS using simple fixed curve electrode catheters is a rather difficult task with uncertain success, although steerable catheters may increase success rates of transfemoral CS catheterization [5,7].…”
Section: Discussionmentioning
confidence: 99%
“…Coronary sinus’ (CS) strategical position between left (LA) and right atrium (RA) allows the detection of non-PV triggers and PV reconnection gaps throughout the atria during CA procedures via CS catheterization [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Despite its extensive use as a CA reference, whether CS analysis could provide reliable information with respect to the AF substrate modification or which channels of CS catheter are the most appropriate for the analysis are two vital issues that remain unexplored.…”
Section: Introductionmentioning
confidence: 99%